Implementasi Metode RAD Pada Perancangan Aplikasi Perpustakaan Berbasis Web (Studi Kasus : SMKN 12 Kabupaten Tangerang) - Abdul Wahab; Rahma Ashara; Julian Andini; Wasis Haryono (CV. Multi Kreasi Media, 2023)
The school library has a big role as a means for students to broaden their knowledge. Because with the library, students can easily find information or knowledge through the library. In this digital era, the availability of computers plays a role as an indicator of the use that must exist in school libraries. The library system used by SMKN 12 Tangerang Regency is to manage data using a conventional system with sheets of paper. This way of managing data requires a lot of time so that the data presented sometimes has changed so that it is not in accordance with reality. To provide a solution to this problem, a web-based application was designed using PHP as the programming language, MySQL as the database processor and Rapid Application Development as the development method. With this system, it is expected to be able to overcome the various needs of users to find books and facilitate school administration in circulating book loans and making reports.